5B.04: TIME TO PEAK SYSTOLIC MYOCARDIAL WALL STRESS IS INDEPENDENTLY ASSOCIATED WITH DIASTOLIC FUNCTION. (June 2015) - Gu, H.; Siinha, M.; Simpson, J.; Chowienczyk, P.
Abstract : Objective: Diastolic dysfunction in hypertensive patients with preserved left ventricular (LV) ejection fraction (EF) (>40%) could be associated with prolonged systolic contraction and delayed systolic relaxation. We therefore examined whether time to peak systolic myocardial wall stress (MWS) relates to diastolic dysfunction. Design and method: We studied 178 subjects, evaluated for hypertension but otherwise free of clinically apparent cardiovascular disease aged 45.8 ± 16.3 (mean ± SD) years with mean systolic blood pressure (SBP) of 139 ± 23 mmHg and EF of 57.9 ± 7.5%. The E/E' ratio was calculated from Doppler echocardiography mitral valve inflow and tissue Doppler of the basal lateral segment and used as a surrogate of diastolic function. MWS, a function of left ventricle (LV) pressure and geometry was obtained using carotid tonometry to estimate LV pressure during systole and 2D transthoracic echocardiographic wall tracking analysis (Tomtec) to derive cavity and myocardial wall volume. Subjects were divided into three groups (Group one (n = 64): SBP < 130mmHg and E/E' < 10; Group two (n = 92): SBP > = 130mmHg and E/E' < 10; Group three (n = 22): SBP > = 130mmHg and E/E' > = 10). Results: EF was preserved and not significantly different between groups (p = 0.44). Time to peak systolic MWS (Group one: 81.4 ± 3.9ms (mean ± SE), Group two 91.8 ± 4.2ms and Group three 116.4 ± 12.2ms) was significantly higher in group three with or without adjustment for age, body surface area (BSA) and HR compared to group one and two (p = 0.001). Across all groups, time to peak MWS was positively associated (standardized β = 0.24, p = 0.001) with E/E' ratio. Conclusions: In hypertensive patients with preserved EF, impaired diastolic relaxation is associated with prolonged ventricular contraction independent of age, BSA and HR.